صورة المرأة في الأمثال الشعبية في منطقة وادي سوف - قعيد فوزية (University of Eloued جامعة الوادي, 2025)
الأمثال الشعبية هي جزء مهم من التراث الشفهي، تعكس تصورات المجتمع وقيمه تجاه العديد من القضايا بما في ذلك من دور المرأة مكانتها، ومذكرة " صورة المرأة في الأمثال الشعبية في منطقة وادي سوف" تتناول دراسة تحليلية لصورة المرأة من خلال الأمثال الشعبية المتداولة في هذه المنطقة، في هذه الدراسة تم تحليل الأمثال الشعبية التي تناولت موضوع المرأة في مختلف الوضعيات والأدور منها: كطرف في الزواج، كأم، كبنت، ككنة، ، كعروس، كزوجة ثانية، كعزوز ، وكمطلقة.. والهدف من المذكرة هو فهم كيف تعكس هذه الأمثال النظرة الاجتماعية للمرأة في وادي سوف Folk proverbs are an important part of the oral heritage, reflecting society's perceptions and values towards many issues including the role and status of women, and the memorandum "The Image of Women in Folk Proverbs in the Wadi Souf Region" deals with an analytical study of the image of women through folk proverbs circulating in this region, in this study, folk proverbs were analyzed that addressed the topic of women in various situations and roles, including: mother, daughter, daughter-in-law, bride, second wife, husband, and divorce: As a party to a marriage, as a mother, as a daughter, as a daughter-in-law, as a bride, as a second wife, as a husband, and as a divorcee. The aim is to understand how these proverbs reflect the social perception of women in Ouadi Sou
دراسة موضوعاتية
أدب شعبي
Keywords: المرأة; الأمثال الشعبية